TG13 management bundles for acute cholangitis and cholecystitis - Okamoto, Kohji; Takada, Tadahiro; Strasberg, Steven M.; Solomkin, Joseph S.; Pitt, Henry A.; Garden, O. James; Büchler, Markus W.; Yoshida, Masahiro; Miura, Fumihiko; Kimura, Yasutoshi; Higuchi, Ryota; Yamashita, Yuichi; et al. (Journal of hepato-biliary pancreatic sciences, 2013)
Bundles that define mandatory items or procedures to be performed in clinical practice have been increasingly used in guidelines in recent years. Observance of bundles enables improvement of the prognosis of target diseases as well as guideline preparation. There were no bundles adopted in the Tokyo Guidelines 2007, but the updated Tokyo Guidelines 2013 (TG13) have adopted this useful tool. Items or procedures strongly recommended in clinical practice have been prepared in the practical guidelines and presented as management bundles. TG13 defined the mandatory items for the management of acute cholangitis and acute cholecystitis. Critical parts of the bundles in TG13 include diagnostic process, severity assessment, transfer of patients if necessary, therapeutic approach, and time course. Their observance should improve the prognosis of acute cholangitis and cholecystitis. When utilizing TG13 management bundles, further clinical research needs to be conducted to evaluate the effectiveness and outcomes of the bundles. It is also expected that the present report will lead to evidence construction and contribute to further updating of the Tokyo Guidelines.
Gesehen am 06.12.2021